The Downside of Fat: Avoiding and Treating Complications - Kim, Irene A.; Keller, Gregory; Groth, Michael J.; Nabili, Vishad (Facial Plastic Surgery, 2016)
Three-dimensional facial volume restoration using fat has become widely accepted as an essential component of facial rejuvenation. Transplanted fat has benefits due to its inherently nonallergenic nature. The versatility of fat grafts allows for their use in all types of facial enhancement—improving the appearance of nasolabial folds, mesolabial grooves, flattened cheeks and upper lips, glabellar furrows, lipoatrophy, acne scars, and temporal hollowing. Yet despite its virtues as the ideal filler, autologous fat has its shortcomings with risks of complications. Our objective in this article is to present a systematic approach demonstrating the complications that can occur with each step of autologous fat grafting in facial rejuvenation and offering pearls to avoid and treat these complications.
Keywords: fat; filler; injection; complication; adipose